Stoichiometry Determination of Chalcogenide Superlattices by Means of X‐Ray Diffraction and its Limits. Issue 4 (22nd February 2019) - Hollermann, Henning; Lange, Felix R. L.; Jakobs, Stefan; Kerres, Peter; Wuttig, Matthias
Abstract : In this paper, the potential of stoichiometry determination for chalcogenide superlattices, promising candidates for next‐generation phase‐change memory, via X‐ray diffraction is explored. To this end, a set of epitaxial GeTe/Sb2 Te3 superlattice samples with varying layer thicknesses is sputter deposited. Kinematical scattering theory is employed to link the average composition with the diffraction features. The observed lattice constants of the superlattice reference unit cell follow Vegard's law, enabling a straight‐forward and non‐destructive stoichiometry determination. Abstract : Chalcogenide superlattices significantly expand the application potential of phase‐change materials and provide unique opportunities to tailor their properties. However, the fabrication as well as the analysis of such superlattice films is challenging. Usually transmission electron microscopy is employed to characterize superlattice samples which needs time‐consuming sample preparation. This investigation provides a straightforward technique to derive the chemical composition and the constituent layer thicknesses from diffraction data only.